The Impact of Head Nurse Supervision and Nurse Motivation on Discharge Planning Compliance at RSUD Dr. M. Haulussy Ambon - Parinussa, Nenny; Manuhutu, Feby; Lameky, Vernando Yanry (Universitas Ahmad Dahlan, 2025)
Discharge planning ensures continuity of patient care after hospitalization, yet in Indonesia, it often faces documentation and procedural challenges. This study examined the relationship between head nurse supervision and nurse motivation with compliance in implementing discharge planning at RSUD Dr. M. Haulussy Ambon. Using a cross-sectional design, data were collected from 257 nurses through validated questionnaires and observation sheets. Findings showed that 64.2% received good supervision, 56.4% had good motivation, and 58.4% demonstrated good compliance. Chi-square analysis revealed significant associations between head nurse supervision (p < .001) and motivation (p = .037) with compliance. Good supervision increased compliance 4.7 times (OR = 4.73; 95% CI: 2.67–8.40), and good motivation increased it 2.9 times (OR = 2.87; 95% CI: 1.16–4.85). These results highlight the importance of structured supervision and sustained motivation to improve discharge planning, enhance patient safety, and reduce readmissions.